CRITICAL THINKING IN HIGHER EDUCATION STUDY PROGRAMS: CASE STUDY - Pivoriene, Jolanta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Social work in its essence has direct relation with critical thinking what is expressed in the Global definition of social work. It is one of the professions which need immediate reaction to unexpected changes in uncertain situations; therefore, it is relevant to discuss critical thinking contribution to the development of social work profession and its presence in social work education. The aim of the article is to discuss importance of critical thinking in higher education and to present data of case study, which reveals how critical thinking is expressed in social work education. Case study was done in country’s one university. Descriptions of all social work study programs subjects’ descriptions were analysed using quantitative and qualitative content data analysis. The analysis of social work study programs at selected university revealed that critical thinking is more expressed in master level than bachelor level social work study programs and it is more described as domain- specific then domain-general, is mentioned in learning outcomes and assessment and very rarely – study methods. The case study identified the gap between formality and reality. Theoretically critical thinking should be part of social work study programs; however, it is wide possibilities for enhancing critical thinking manifestation in the reality of teaching and learning.